Estratégias para a utilização de dispositivos móveis na educação infantil: utilizando aplicativo Digital Storytelling - Machado, Ana Paula Rodrigues (2021)
This study is linked to the research link Management of Educational Network Technologies, the Graduate Program in Network Educational Technologies and the Interdisciplinary Research Group in Education at the Federal University of Santa Maria / RS, and addresses the theme that refers to pedagogical practices mediated by digital technologies in Early Childhood Education and its relevance to the educational area. The ability to interact, adapt and create digital narratives meaningly benefits the child's development process in early childhood, providing them with fun and playful experiences and learning with the use of digital technology. Therefore, this study had the general objective of investigating how the use of mobile devices and digital technology occurs, backing the process of development and learning of children in Early Childhood Education, considering the learning rights proposed in the National Common Curricular Base - BNCC, Child education. To this end, the methodology involved applied research, with a qualitative approach, of an exploratory-explanatory type, and as for the procedures, this study starts from a netnographic research design. The locus of the research is a Public School, located in the inland of Rio Grande do Sul, having as subjects, four teachers, six scholarship holders and a child. For data collection, the online questionnaire was used, composed of open questions. To this end, three categories of analysis were listed, which are: Digital Storytelling Toontastic 3D App, Learning Rights, Technology and Early Childhood Education. The analysis of the results of this investigation was theoretical-explanatory and took place, based on an inductive approach to the analysis of qualitative data. Finally, the conclusions point to four directions: the re-signification of teaching practice to the use of digital technologies in Early Childhood Education, the need for teacher training in the use of ICT, the importance of the face-to-face teaching model for child development processes in Early Childhood Education and the development of strategies that enhance pedagogical practice and ensure the learning rights proposed by BNCC. Resulting from this study, the master's product consists of a Digital Educational Material - MED developed during the research to assist the participants during remote teaching, the strategies for the use of mobile devices and digital technology in Early Childhood Education, contemplating the proposed learning rights at the National Common Curricular Base - BNCC and a pedagogical proposal model. And as a perspective for future work, there is a proposal for training teachers in digital technologies with an online course that will be offered to research participants and other teachers and educators of the studied institution. So, the procedure of insertion of mobile digital technologies and digital applications contributes to the innovative educational process, creating strategies for its use in an efficient and meaningful way, enhancing the learning processes. It is expected that teacher training will provide the inclusion of digital technologies in education, such as mobile devices and digital apps, which ensure children's learning and playing rights in rich and challenging proposals, promoting quality education and digital inclusion and educational experience of all children.